Exploring affective Polarisation of the (Digital) Public Sphere in Slovenia: The Case of Marshal Twito - Mahmutović, Melika; Lovec, Marko (Javnost-The Public, 2024)
The last decade saw the issue of polarisation garnering increased scholarly attention. While political polarisation has been almost unequivocally studied as synonymous with ideological polarisation, scholars have recently addressed polarisation along partisan lines manifesting through strong in-group favouritism and out-group unfavouritism, labelled as affective polarisation. This paper investigates patterns of affective polarisation in the Slovenian (digital) public sphere, through analysis of discourse of former Slovenian PM Janez Janša on Twitter. The affective-discursive analysis of Janša’s Twitter resulted in the identification and exploration of four affective-discursive practices: Dangerous Outsider, Pride and Patriotism, Immoral and Incompetent Women and Defection. We find that through interplay of these practices and by employing strategies of discursive closure, Janša successfully fuels polarisation among partisans by solidifying divisions along the in-group-out-group axis. The paper contributes to affective polarisation literature by demonstrating how political actors condition competitive environments around different social identities thereby minimising opportunities for meaningful deliberation and debate beyond the differences.